A study on the factors influencing old age identity among the Chinese elderly - Xiao Yu; Xiao Yu; Qihui Wang; Qihui Wang (Frontiers Media S.A., 2023)
BackgroundOld age identity is the self-perception of when old age begins, reflects public age values and acceptance of aging. Not all elderly people aged 60 and above identify with their old age status. The aging society in the traditional sense may not be "aging". Therefore, redefining old age is crucial. Different from Western countries, China is a country with a long-standing culture of respect for the elderly and filial piety norms, and the influence of the cultural background on the old age identity is worthy of attention.Data and methodData were drawn from the 2014 China Longitudinal Aging Social Survey (CLASS). A total of 7400 participants answered questions about old age identity. Based on old age identity, we obtained two other types of indicators of perceived old age: elderly group identity and aging degree. For the continuous variable old age identity and aging degree, an OLS linear regression model was established. A binary logistic regression model was established for the binary variable elderly group identity.ResultThe average old age identity of Chinese people aged 60 and above is 70 years. Health status, psychological status, behavior, socioeconomic status, and some demographic characteristics significantly affect the old age identity of the Chinese elderly.ConclusionThe traditional Chinese cultural background of respect for the elderly and the norms of filial piety have an impact on the old age identity of the Chinese elderly through family intergenerational support. The various forms of support provided by children to the elderly can help them achieve a positive age identity-enter old age later, raise the likelihood of identification with non-elderly groups, and reduce aging degree. The number of children of the elderly, the children's economic conditions and care support for grandchildren have negative effects. A positive old age identity can help the elderly improve their self-esteem.